Pengelolaan Keuangan Terhadap Laporan Keuangan Umkm Bakso “Cak NOS” - Dian Rimayanti; Prisca Trifena Puspita; Sinta Tri Hapsari; Chava Annastasia Candra; Achmad Alfin Nahdi Fadhulloh; Sri Rahayuningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The Indonesian economy is one of the most dynamic in Southeast Asia and the pioneer of the largest economy in Indonesia is UMKM. (Usaha Mikro, Kecil, dan Menengah). UMKM can be a means of determining the financial level of the community. With the presence of small, jobs will increase and indirectly contribute to the decline in unemployment in Indonesia. As for UMKM, the constraints faced today are the number of entrepreneurs who are often unable to create and display data to review the state of development of their business, especially related to the processing of reports and budgets. Good financial-related processing includes financial position reports, and profit and loss reports, but in fact there are still many business players who do not have a systematic, structured foundation and minimal knowledge of financial management. Based on financial position reports, profit and loss reports, and records on financial statements, UMKM Bakso Cak Nos in Surabaya City does not implement adequate accounting systems due to limited human resources in accounting knowledge and skills. Improvements in financial reporting are needed to provide accurate and useful information in economic decision-making.